PEMANFAATAN TUMBUHAN SEBAGAI BAHAN PANGAN DISEKITAR KAWASAN HUTAN DESA SEDAHAN JAYA KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Irawan, Ria; Oramahi, H A; Hardiansyah, Gusti (JURNAL HUTAN LESTARI, 2020)
Food plants are all things that grow alive, stemmed, rooted, leafy and can be eaten or consumed by living things. The food plants can be in the form of seeds, fruits, vegetables and tubers which are one of the basic human needs besides clothing and shelter. The purpose of this study is to list the types and parts of plants as well as processing methods which is used as food by the people of Sedahan Jaya Village, Sukadana District, North Kayong Regency. The method used in this study is a survey method. Data collection using Snowball sampling technique with interviews and questionnaires. Based on the results of research on the utilization of food plants in Sedahan Jaya Village, Sukadana Subdistrict, North Kayong Regency, found 48 types of food plants, based on the family found 26 families and what Dominates of family is Moraceae. Fruit is the most commonly found, which is 36 species (75%). Based on the method of processing, direct consumption is the most commonly found method, as many as 25 types (52.08%). Based on habitus, trees are the most commonly found, as many as 29 species (60.41%). Based on the type of food group food group, the most commonly found fruits are 29 types (60.41%). And based on the status of the place to grow, wild plants were found the most as many as 38 species (79.16%).Keyword : food plants, part of plant, processing, Sedahan Jaya village, utilization